Pengembangan Media Pembelajaran Aplikasi Android Interaktif Berbasis Software Ispring Suite di SMK Muhammadiyah 1 Kota Sukabumi - Desi Hilwana; Heni Wulandari; Lutphi Saepuloh (Jurnal Ilmiah Wahana Pendidikan, 2022)
Learning is all efforts made by a teacher (educator) to ensure that the learning process takes place in students. The learning process is a communication process to convey messages or materials. Learning materials require appropriate learning media so that the learning process goes well and students can understand the messages and materials conveyed by the teacher. Learning technology aims to encourage learning and improve performance by creating, using, or utilizing and managing appropriate technological processes and resources. Android devices can also develop into interactive learning media that are useful for students. This study aims to produce products in the form of interactive android application learning media that are suitable for use for learning. The type of research used is research and development of R&D with reference to research and development by Borg and Gall which consists of ten stages of data collection used by researchers are interviews with subject teachers, and through classroom observations to students. Meanwhile, the method of collecting data is through a questionnaire based on media from material experts, media and design experts, and user ratings. The results showed that the material expert validation obtained a 90% presentation in the very appropriate category. The media expert validation results obtained a presentation of 88% in the very feasible category and field trials by students scored 90% in the "very feasible" category. Thus, it can be concluded that this learning media product is said to be very suitable for use in student learning.